Migrant protest : interactive dynamics in precarious mobilizations - Steinhilper, Elias (Protest and social movements., 2021)
Migrant protest has proliferated worldwide in the last two decades, explicitly posing questions of identity, rights, and equality in a globalized world. Nonetheless, such mobilizations are considered anomalies in social movement studies, and political sociology more broadly, due to 'weak interests' and a particularly disadvantageous position of 'outsiders' to claim rights connected to citizenship. In an attempt to address this seeming paradox, this book explores the interactions and spaces shaping the emergence, trajectory, and fragmentation of migrant protest in unfavourable contexts of marginalization. Such a perspective unveils both the odds of precarious mobilizations, and the ways they can be temporarily overcome. While adopting the encompassing terminology of 'migrant', the book focusses on precarious migrants, including both asylum seekers and 'illegalized' migrants.